Removal of Pb2+ from aqueous solution by adsorption onto composite based on eucalyptus leaf and polyaniline - The, Le Cao; Tan, Vu Minh; Binh, Phan Thi (Vietnam Journal of Science and Technology, 2017)
Composite based on eucalyptus leaf and polyaniline (EL-PANi) was prepared by chemical polymerization method. It showed that the function groups belonging to polyaniline and eucalyptus leaf were found through IR analysis and the nanostructure of composite was explained by SEM images. The adsorption of  Pb2+ was carried out onto composite in aqueous solution via varying pH, contact time, and its initial concentration. The experimental adsorption data fitted well into Freundlich adsorption isotherm model (r2 = 0.9873). The adsorption process followed pseudo-second order kinetic with r2 = 0.9995. The maximum adsorption capacity of Pb2+ onto that composite was 172.4138 mg/g  by Langmuir equation and KF was 58.7527 mg/g by Freundlich one.